Identifying the Effects of Place-Based Policies - Causal Evidence from Germany - Eva Dettmann; Matthias Brachert; Mirko Titze (Center for Economic Studies and ifo Institute (CESifo), 2016)
The German government provides discretionary investment grants to structurally weak regions to reduce regional disparities. We use a regression discontinuity design that exploits an exogenous discrete jump in the probability of receiving investment grants, to identify the causal effects of the investment grant on regional outcomes. We find positive effects for regional gross value-added and productivity growth, but no effects for employment and gross wage growth.
Keywords: Z00; A11; D61; H20; 330; evaluation; industrial policy; regression discontinuity design